2021
DOI: 10.1016/j.bioactmat.2021.04.013
|View full text |Cite
|
Sign up to set email alerts
|

In situ bone regeneration with sequential delivery of aptamer and BMP2 from an ECM-based scaffold fabricated by cryogenic free-form extrusion

Abstract: In situ tissue engineering is a powerful strategy for the treatment of bone defects. It could overcome the limitations of traditional bone tissue engineering, which typically involves extensive cell expansion steps, low cell survival rates upon transplantation, and a risk of immuno-rejection. Here, a porous scaffold polycaprolactone (PCL)/decellularized small intestine submucosa (SIS) was fabricated via cryogenic free-form extrusion, followed by surface modification with aptamer and PlGF-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 48 publications
1
44
0
Order By: Relevance
“…Some researchers reported that dense and mature newly-formed fibrous tissue and new blood vessel in H&E staining and Masson staining indicated better bone regeneration and angiogenesis. 48 , 49 …”
Section: Discussionmentioning
confidence: 99%
“…Some researchers reported that dense and mature newly-formed fibrous tissue and new blood vessel in H&E staining and Masson staining indicated better bone regeneration and angiogenesis. 48 , 49 …”
Section: Discussionmentioning
confidence: 99%
“…However, gaining bone regeneration at large bone defects parts is still challenging. Therefore, recently, genes and/or RNAi modified osteoinductive artificial scaffolds (Laird et al, 2021;Sun et al, 2021) and genetically arranged high functional cell seeded scaffolds (Sato et al, 2018;Gugliandolo et al, 2021;Jiang et al, 2021) have been considered as new upcoming bone regeneration strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Aptamers exhibit high specificity and affinity for target ligands without inducing immunogenic or toxic effects. Compared to other targeting agents, such as antibodies, chemokines, GFs, and peptides, aptamers possess greater temperature and pH stability and exhibit a high circulation clearance rate 16,17 . Recently, researchers have sought to utilize aptamers as therapeutic agents for the recognition and capture of MSCs for tissue engineering applications.…”
Section: Introductionmentioning
confidence: 99%